The Criminal Policy in Efforts to Overcome Crimes Perpetrated by the Indonesian National Army - Yulianto Timang; Widayati Widayati; Nanang Sri Darmadi (Universitas Islam Sultan Agung, 2022)
This study aims to find out and analyze and seek answers to criminal policies in an effort to tackle crimes committed by the Indonesian National Armed Forces and to find out and analyze and seek answers to policies for regulating criminal law enforcement against TNI soldiers in the future. The results and discussion of the research show that Criminal Policy in Efforts to Overcome Crimes Committed by the Indonesian National Armed Forces is subject towetboek van Militair Strafrecht (WvMs)/Stb.1934 Number 167 in conjunction with UURI Number 39 of 1947, which was translated into the Military Criminal Code (KUHPM). Its enforcement is the same as in law in Indonesia, if the Criminal Procedure Code is a material criminal law, then Act No. 6 of 1950 in conjunction with Act No. 1 Drt of 1958 concerning Military Criminal Procedure Code which was later revised and set forth in Chapter IV of Article 264 of the Law. Law on Military Courts, while Act No. 31 of 1997 applies as a formal criminal law, and the realization of the revision of Act No. 31 of 1997 concerning Military Courts. Criminal Law Enforcement Against Indonesian National Army Soldiers in the Future.